Replacing Dietary Fish Meal with Defatted Black Soldier Fly (Hermetia illucens) Larvae Meal Affected Growth, Digestive Physiology and Muscle Quality of Tongue Sole (Cynoglossus semilaevis) - Li, Xueting; Qin, Chuanjie; Fang, Zhenzhen; Sun, Xueliang; Shi, Hongyue; Wang, Qingkui; Zhao, Honghao (Frontiers in Physiology, 2022)
For solving the global shortage of fish meal (FM) supplies from fisheries, black soldier fly (Hermetia illucens) has become a new protein alternative in aquatic feeds. The present study investigated the effects of inclusion of defatted H. illucens larvae meal (DBLM) on growth, serum parameters, digestive function and muscle quality of tongue sole (Cynoglossus semilaevis). The feeding experiment consisted of five experimental diets: a control diet based on FM protein (H0), four DBLM diets, substituting 25% (H25), 50% (H50), 75% (H75) and 100% (H100) of FM. C. semilaevis were randomly allocated over five treatments. After 65-day feeding, the weight gain rate (WGR), specific growth rate (SGR) and protein efficiency ratio (PER) were significantly higher in H0 and H25 groups with less feed conversion ratio (FCR) and feed intake (FI). The serum ALT, TG, T-CHO, ALB, GLO and ratio (A/G) in H25 group were also significantly higher than those in other DBLM diets-feeding groups. The digestive enzyme activities firstly increased (from 25% to 75%), then decreased (since 75%) with increased level of DBLM in diets. Meanwhile, there were significant improvements in thickness of intestinal longitudinal muscle (LM), circular muscle (CM), columnar epithelium (CE) and lamina propria (LP) in H25 compared to H0 (P < 0.05). The fish from other DBLM diets groups presented significant reductions in thicknesses of LM, CM, CE and LP, as well as the length of microvilli (ML) by a dose-dependent manner (P < 0.05). However, the substitution of FM increased up to 50% would result in intestinal structural damage. Moreover, the proximate compositions, antioxidant and water holding capacity, muscular structures of fish fillets were all significantly affected after substituting 25% FM (P < 0.05). Except for DM, moisture, ash, CF and CP contents were significantly higher in H25. The SOD activity in H0 was greatly lower than that in H25. The CAT activity prominently reduced along with the raise in DBLM content in diets (P < 0.05). The water holding capacity of C. semilaevis fillets was best in H25 group. In summary, the optimum proportion of DBLM with FM for feeding C. semilaevis may around 25%.